State-of-the-art analysis of quantum cryptography: applications and future prospects - Sahu, Swastik Kumar; Mazumdar, Kaushik (Frontiers in Physics, 2024)
Quantum computing provides a revolution in computational competences, leveraging the principles of quantum mechanics to process data in fundamentally novel ways. This paper explores the profound implications of quantum computing on cryptography, focusing on the vulnerabilities it introduces to classical encryption methods such as RSA and ECC, and the emergence of quantum-resistant algorithms. We review the core principles of quantum mechanics, including superposition and entanglement, which underpin quantum computing and cryptography. Additionally, we examine quantum encryption algorithms, particularly Quantum Key Distribution (QKD) protocols and post-quantum cryptographic methods, highlighting their potential to secure communications in the quantum era. This analysis emphasizes the urgent need for developing robust quantum-resistant cryptographic solutions to safeguard sensitive information against the imminent threats posed by advancing quantum technologies.